Outriders : rodeo at the fringes of the American West - Scofield, Rebecca (University of Washington Press, 2019)
"This book examines how (and why) rodeo has provided diverse communities ways in which they can prove themselves as real Americans, real men, and real heroes, often through the enactment of ever-shifting concepts like authenticity, tradition, and heritage. The author analyzes how the space of the rodeo arena has exposed fractures in the narrative of the cowboy over the twentieth century, focusing particularly on the experiences of non-normative cowboys and cowgirls to demonstrate how people stripped of their place in a collectively imagined Western past have both challenged and reinforced the cowboy as an icon of American authenticity. The case studies include female bronc-riders in the 1910s and 1920s, convict cowboys in the mid-twentieth century, all-black rodeos in the 1960s and 1970s, and gay rodeoers in the late century. Cast out of popular Western mythology and pushed to the fringes in everyday life, these people found belonging and meaning at the rodeo, staking a claim to national inclusion through regional performance. Yet, alongside their challenges to the restrictive definition of the cowboy, they also contributed to the persistent idea of an authentic Western identity"--